Advanced Atomic Layer Deposition Technologies for Micro-LEDs and VCSELs - Yen-Wei Yeh (SpringerOpen, 2021)
Abstract In recent years, the process requirements of nano-devices have led to the gradual reduction in the scale of semiconductor devices, and the consequent non-negligible sidewall defects caused by etching. Since plasma-enhanced chemical vapor deposition can no longer provide sufficient step coverage, the characteristics of atomic layer deposition ALD technology are used to solve this problem. ALD utilizes self-limiting interactions between the precursor gas and the substrate surface. When the reactive gas forms a single layer of chemical adsorbed on the substrate surface, no reaction occurs between them and the growth thickness can be controlled. At the Å level, it can provide good step coverage. In this study, recent research on the ALD passivation on micro-light-emitting diodes and vertical cavity surface emitting lasers was reviewed and compared. Several passivation methods were demonstrated to lead to enhanced light efficiency, reduced leakage, and improved reliability.